FOMO GENERASI Z: PERAN TREN DIGITAL DALAM MEMBENTUK KECEMASAN DAN KEPUASAN DIRI - Putri Hayat; Nurhanifa Nurhanifa; Gracia Tabitha Ardihya; Desma Yuliadi Saputra (Jurnal Ilmiah Penelitian Psikologi, 2026)
The phenomenon of fear of missing out (FoMO) has become increasingly prevalent among Generation Z in parallel with the intensive use of social media and the rapid evolution of digital trends. This study aimed to explore the lived experiences of FoMO among Generation Z and to identify digital factors contributing to its occurrence. A descriptive qualitative approach was employed, involving 10 informants aged 18–25 years, with data collected through semi-structured interviews. The findings indicate that high exposure to viral content, online social activities, and idealized lifestyle portrayals increases susceptibility to FoMO, which manifests in emotional anxiety, digital social pressure, impulsive consumptive behavior, and fluctuations in self-satisfaction. However, several informants demonstrated effective self-regulation strategies, such as limiting social media use and strengthening self-identity, to mitigate FoMO. These results highlight the importance of enhancing digital literacy and self-regulation skills as strategic efforts to reduce the negative psychological impacts of FoMO among Generation Z. Keywords: Digital Trends, FoMO, Generation Z, Psychological Well-being, Social Media